Secure and Efficient Distributed Relay-Based Rekeying Algorithm for Group Communication in Mobile Multihop Relay Network - Adnan, Shahid Khan (Kohat University of Science and Technology (KUST), Pakistan, 2014)
In mobile multihop relay (MMR) networks, Relay multicast rekeying algorithm (RMRA) is meant to ensure secure multicast communication and selective updating of keys in MMR networks. However, in RMRA, the rekeying is carried out after a specific interval of time, which cannot ensure the security for multicast communication on joining the member. Secondly, the rekeying scheme generates a huge communication overhead on the serving multihop relay base station (MR-BS) on frequent joining of members. Lastly, there is nothing about when a member left the group communication. Thus, the rekeying scheme of RMRA fails to provide forward and backward secrecy and also is not scalable. To solve this problem, an improved rekeying scheme based on broadcasting a new seed value on joining and leaving of a member for updating the ongoing key management is proposed. The proposed scheme solves the issue of forward and backward secrecy and the scalability in a very simplified way. The forward and backward secrecy of the proposed scheme has been extensively validated by formal method using rank theorem. Furthermore, mathematical derivation showed that the proposed scheme out-performed the RMRA in terms of communication cost and complexity.